The Rhizosphere and its Impact on the Distribution of Soil Bacteria - Azzouz, A.A.; Endar, A.M.; El- Tarhuni, A. I. El- Tarhuni (Al-Mukhtar Journal of Sciences, 1992)
The gram-negative species of soil bacteria outnumbered the remaining bacterial population in the rhizosphere. Soils surrounding this region showed dominance of gram-positive cocci, endo- spore forming rods and thread-like spe- cies of the Actinomycetes. Plant type and its stage of maturity does not effect the above general distribution, except the sense of altering species make-up. in Non-symbiotic nitrogen-fixing bacte- ria of the genus Azotobacter prevail in the rhizosphere of the four tested crops, particularly in the early stages of plant development (seedling-stage). The changes in the trend of the cal- culated ratio of gram-negative bacteria in the rhizosphere to that of the sur- rounding soil can not be generalized to all species. Results obtained with Azot- obacter population showed different picture.